True life in Uncanny Valley - Caletti, Deb (Labyrinth Road, 2025)
"Eleanor, like so many others, is used to watching her famous father from afar. To the world, Hugo Harrison is the brilliant and charismatic tech genius whose AI inventions seem to create a new, better reality. But to Eleanor, whose mother had an affair with Hugo years ago, he is something even more intriguing, and dangerous--a secret. When Eleanor's spying leads her to a posting for a live-in summer nanny job for Hugo's young son--her half-brother--she knows she has to apply. This is finally her chance to learn about her father, his family, and the life that could have been hers. She only has to do one thing: become someone else. With just a few well-placed lies, Eleanor is catapulted into an unfamiliar, intoxicating whirlwind of money and ego, and into a new romance with a cute boy who works for Hugo. But in a place where image is everything and reality can be rewritten, is anything real--even the Harrisons themselves? Caught between her own secrets and the ones she's uncovering about her father and his latest invention, Eleanor faces a question that technology can't answer: what is your true self, and how do you know when you find her?"--